Pengembangan Multimedia Interaktif pada Pembelajaran IPA bagi Siswa Sekolah Dasar Kota Lubuklinggau - Asep Sukenda Egok; Tri Juli Hajani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The study aims at producing the valid, practical, interactive and potential multimedia to teach science to students achievement at the fifth grade elementary school in Lubuklinggau. The procedure of the study was through Rowntree model including three steps, namely planning, developing and evaluation. The evaluation stepnm used was Tessmer formative evaluation. The result of the material, media and design validation showed that interactive multimedia was valid. In one-to-one test, the students respond positively toward the interactive multimedia. In tryout step on the small group, it categorized as practical. In the field test, it was categorised as medium with score 79,11. It can be concluded that interactive multimedia was developed in the study was valid, practical and potential on students science learning achievement at the Elementary School. Keywords: interactive multimedia, science learning